Biopsy sampling of red muscle does not affect physiological performances in rainbow trout - Morgane Pengam; Asrar Lehodey; Patrick Calvès; Jean-Baptiste Quéméneur; Karine Salin; Bernard Simon; Aline Amérand (Aquaculture Reports)
Muscular biopsy is a non-lethal muscle sampling technique allowing for the fish to be returned to its natural environment or its tank after sampling. This technique offers the opportunity for the scientific community and fish farmers to carry out assays on very small muscle samples (between 1 and 40 mg) such as heavy metal, trace elements, lipid composition or muscle energetic metabolism to evaluate, for instance, the health of the fish. The aim of the present study was to determine if a red muscle biopsy affects rainbow trout (Oncorhynchus mykiss) survival and their physiological performances (swimming and hypoxia resistances). Each group, fish that had a biopsy (n = 30) or fish that did not (n = 30), was subsequently tested for either a hypoxia resistance test (HRT) or a swimming resistance test (SRT). HRT and SRT were conducted 7- and 10-days post-surgery (dps), respectively. Biopsy had no effect on hypoxia resistance and on swimming parameters (sustained and critical swimming speeds, tail beat frequency, routine and maximal oxygen consumptions). Even if no significant effect was observed between control and biopsy groups on morphometric parameters (body weight variation and condition factors), all the trout lost weight which can be explained by a post-surgery trauma such as human manipulation stress or a local inflammation. More specifically, body weight variation was significantly more important in the 7-dps group compared to the 10-dps group which had the opportunity to eat three more days compared to the 7-dps group. Corroborated with a principal component analysis, we showed that a red muscle biopsy is a good approach as it had no effect on whole-animal performance 7- and 10-dps and it had no effect their survival.